Telenovela: o olhar capturado - construcao da triade telespectador, corpo e imagem - Apostolico, Cimara (2006)
This research analyses the soap opera in its aspects related to the image presentation as hegemonic item in the audience s ability to perceive things. It is chosen to understand soap opera not in its aspects of daily narratives, but as imagery narratives created by bodies that represent themselves as mediators in the process of communication, functioning as main starting-point in the image production. In this way, the concept of body and body language is used. With it this process starts, expressing the relation of cumulativity and complementarity to media, reinforcing the soap opera appealing. It is perceived that the body is seen on the soap opera as commodities and exploiting fact. This paper/thesis selects the male image because of the visible set of public opinion in the last years. The questions of body image through history are investigated in order to understand in a broad sense its changes in relation to cultural process and trying to highlight the evidences that lead to see it as emerging bodies. The images are narrated/described from the understanding of their origin to questions that point out their symbolic aspects, which belong to the sensibility that creates links among bodies. Using Harry Pross, Martin Barbero, Esther Hamburger, Denise Bernuzzi de Sant Anna, Régis Debray as theoretical support, it can be seen that along with the soap opera several media are used as a support of it. In this sense, magazines that write about cinematographic and TV celebrities are analyzed. Being aware that there is no TV without bodies before and off cameras, for example, biological bodies and body-image, we understand that is in the relation among audience, body and image that the soap opera keeps on